Investigation of the Normal Blowing Approach to Controlling Wingtip Vortex Using LES - Yubiao Jiang; Wanbo Wang; Chen Qin; Patrick N. Okolo; Kun Tang (International Journal of Aerospace Engineering)
The characteristics and control of a wingtip vortex are of great significance when considering drag reduction and flight safety of transportation aircrafts. The associated aerodynamic phenomenon resulting from rolling up of a wingtip vortex includes boundary layer flow, shear layer separation, and vortex breakdown, while the interaction of a wingtip vortex with the airframe causes induced drag, wingtip noise, etc. This paper studies a normal blowing method utilized to control the wingtip vortex. Large eddy simulation (LES) technique applied to a straight NACA0012 wing having a chord length (c) of 0.4 m is adopted for this study. The Reynolds number based on the chord length is 1.6×106 and the angle of attack is 12°. The computational approach utilized the dynamic Smagorinsky-Lilly subgrid model for 3D simulations. Normal blowing from a high aspect ratio jet from the wingtip lower surface was used to control the wingtip vortex. From 0.05c to 0.30c, the blowing slit width was 1 mm, with the slit exit treated as a velocity inlet boundary condition which supplied the blowing jet with a momentum coefficient of 0.28%. Results of axial velocity and span-wise pressure distribution of the clean airfoil presented good agreement with known experimental data. LES results indicate that normal blowing suppresses the primary vortex strength, while the vortex core radius, maximum induced velocity, axial vorticity flux, and pressure peak of the primary vortex are reduced by 25%, 28%, 46%, and 52%, respectively. Flow field structures before and after blowing show that blowing suppresses the shedding, coiling, and convergence of the free vortex layers near the primary vortex. This study also shows that normal blowing generates a jet-induced vortex at the location of the secondary vortex, while backflow, volume expansion, and spiral burst can be observed in the jet-induced vortex. The bursting jet-induced vortex destroys the jet-like flow structure of the primary vortex at the trailing edge.